Membangun Kualitas Jasa Layanan Publik Berorientasi Pelanggan: Suatu Telaah Teoritis - Prayugo, Arlis (Sekolah Tinggi Ilmu Pemerintahan Abdi Negara, 2017)
The purpose of this paper is to examine the theoretical understanding of the quality of services to the public oriented services to customers. Where the existing theory developed to support the development of the existing problems related to the quality of public services for customer oriented. This writing method uses literature analysis, using the book as a writing journal development theoreticians and analysis in order to develop the theory to be more effective in practice in the use of public services. The results of writing is that in order to establish good governance in generating public services then it is very important to note that the community as a customer is the center of attention of the services. Because of the community who could ultimately assess and appreciation for services rendered. The implication of this paper is expected after reading the understanding of the public services oriented to customer satisfaction has increased. Particularly in the bureaucracy of government services. DAFTAR PUSTAKABudi setiono. 2002. Jaring Birokrasi tinjauan dari aspek politik dan adminitrasi. Bekasi : Gugus press.Budiono. 2003. Pelayanan Prima Perpajakan. Jakarta : Rineka Cipta.Christopher Lovelock. 2004. Service marketing : people, technology, strategy. United state : Pearson educational international.Craigh cocharn. 2003. Customer satisfaction : tools technique, and formulas for succes. United states : Paton Professional Press CA.Dale H. Besterfield. 1995. Total quality management. New Jersey : Prentice Hill.Delly Mustafa. 2014. Birokrasi Pemerintahan. Bandung : AlfabetaDwiyanto, Agus (ed), 2014, Mewujudkan Good Governance Melalui Pelayanan Publik, Yogjakarta : Gajah Mada University Press & Japan International Cooperation Agency.Dwiyanto, Agus, 2015, Reformasi Birokrasi Kontekstual : kembali ke jalur yang benar, Yogyakarta : Gajah Mada University Press & LAN (Lembaga Administrasi Negara).Fitzsimmons, James A. 2004. Service Management, opera-tions, strategy, information technology. New york: Mc Graw Hill Companies.Francis Buttle. 2004. Customer relationship management, con-sept and tool. Oxford, Burlington : Jordan Hill.Frank M. Gryna, R. C.H. Chua, J. A. Defeo. 2007. Juran’s Quality Planning and analysis. New york : Mc Graw-Hill.Hanif Nurcholis. 2005. Teori dan praktik Pemerintahan dan Otonomi Daerah. Jakarta : Grasindo.Herdiyansyah. 2011. Kualitas Pelayanan Publik : Konsep, Dimensi, Indikator dan Implementasinya. Yogyakarta : gavamediaKausar. 2009. Sistem Birokrasi Pemerintahan Daerah dalam Bayang-bayang Budaya Patron Klien. Bandung : Alumni.M.N. Nasution. 2004. Manajemen Jasa Terpadu. Bogor : Ghalia IndonesiaMiftah Thoha. 2003. Birokrasi dan Politik di Indonesia. Jakarta : Raja GrafindoOsbore, David & Ted Gaebler, 1995, Mewirausahakan Birokrasi (Reiventing Government) Mentrans-formasi Semangat Wirausaha Ke Dalam Sektor Publik, Jakarta:Pustaka Binaman Pressindo.Philip kotler & Amstroong. Principle of marketing. 2001. New jersey : Prentice-Hall international.Philip Kotler. 2001. A Frame Work for marketing management. New Jersey : Prentice Hill.Ricard L. Oliver. 1997. A behavioral Perpective on the customer. New jersey : Mc Graw-Hill.Valarie A. Zeithaml & Mari Jo B. 1996. Service Marketing. The McGraw-Hill Companues, Inc.Zaenal, M. & Muhubudin Wijaya. L, 2015. Manajemen Pelayanan Publik. Bandung: Pustaka setia.